From the country to the city: tensions between tradition and modernity in an afro-descendant community in the township of Cerrito, Valle del Cauca, Colombia (REVISTA NODO, 2012)
The article deals with the tensions between tradition and modernity faced by an afro-descendant community in the township of Cerrito, Valle del Cauca, specifically those related to cultural practices towards everyday sexuality. Having migrated from diverse rural contexts to this urban scenario, the community subject of research changed its geographical location as well as its place of residence, but its customs and beliefs remained intact. From this point of view, a new problem has arisen that stands in the way of women’s sexual and reproductive rights, namely, male partners refusing to use any birth control method. Accordingly, the issue around this practice demands a historical revision of sexuality in afrodescendant populace from an interpretative perspective that allows for studying how cultural devices are inherited and duplicated in these communities.
Keywords: Sexual and reproductive rights; genre-based violence